Strategi Kehumasan Dalam Pelayanan Informasi Publik - Surtika, Memi; Darwis, Yuliandre (CV. ITTC INDONESIA, 2024)
This research aims to reveal public relations strategies in providing public information services in the Government Management Study of State Administration Institutions (Puslatbang KMP LAN). According to research conducted by (Sri Kartika), Data were acquired through the methods of observation, interviews, and documentation studies, followed by analysis utilizing techniques such as data reduction, data presentation, and drawing conclusions. The research findings indicate that in the following aspects: 1) problem definition - issues managed by public relations in the media are not fully understood by stakeholders, resulting in incomplete information transmission; 2) planning and programming - public relations collaborates with teacher facilitators to introduce and interconnect various social media platforms; 3) action and communication - public relations engages in two-way communication with stakeholders, employing both electronic and non-electronic media to include the public in news channels. Various public media are utilized to disseminate issues, ensuring stakeholders are aware of all channels and can access comprehensive and up-to-date information.